Analisis Sistem Pengendalian Internal Terhadap Proses Keluar – Masuk Barang PT. Global Transportindo Prima - Safitri, Dwi Tika; Suhariyanti, Suhariyanti; Syaharman, Syaharman (Worksheet : Jurnal Akuntansi, 2023)
The number of damaged and lost goods has increased, this is due to the lack of supervision carried out by the company in sorting goods that are easily broken or goods that are easily damaged by using packaging that is easily damaged, the lack of information system procedures in inputting data to prepare reports on incoming goods and out, causing an increase in the loss of goods to be sent, causing the company to have to provide compensation to customers who have lost goods and can cause a decrease in the quality of supervision of the company. Therefore, PT. Global Trasportindo Prima requires an effective and efficient information system so that it can adapt to demands to increase the speed of the process from receipt, storage, to final receipt. The research method was carried out using descriptive analysis method, this research was used to collect research data that would be obtained from PT. Global Transportindo Prima. The results of the study show that PT Global Transportindo Prima has been effective in its internal control over the incoming and outgoing goods process because it has complied with the internal control components of the COSO (committee of sponsoring organization). From the results of the above research it can be concluded: The loading and unloading process carried out at PT Global Transportindo Prima is in accordance with the procedures set by the company. Even though there were several processes that were not carried out because they were adjusted to the actual conditions that existed, overall they had complied with the existing procedures. PT Global Transportindo Prima still had not implemented a good information system so that manual recording would sometimes hamper and lack of manpower so that checking the stock of goods still uses physical files or even checks the items that are arranged. In the management of PT Global Transportindo Prima, there are many who make loans but forget to repay debts, this is due to the transfer of salaries that go to the bank.Keyword : Internal Control System